Nilai Pedagogis Kristen dari Budaya Pasue dalam Perayaan Kalela sebagai Dasar Moderasi Beragama bagi Masyarakat Pulau Ndao - Daud Saleh Luji (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The purpose of this article is to explain the meaning and Christian pedagogical value of Pasue culture in the lives of the Ndao people which is the basis for religious moderation on Ndao Island. To achieve this goal, the method used is a qualitative method with an auto ethnographic approach. The data collection technique used was interviews with 5 community leaders. The research results show that Pasue culture is a culture that has existed for a long time, and is practiced in the Ndao Island community (Ndao people). At a certain time, namely before the harvest season, there is a Kalela tradition, which is a tradition of visiting friends from one village to another bringing provisions from the harvest. The Christian pedagogical values contained in this culture are: 1) Friendship knows no boundaries, just as Christ called us his friends; 2) Friendship begins with a bond of promise and promises must be steadfast; 3) Chickens are cut and blood Chicken is a symbol (of life) that is shed for togetherness, therefore it must be maintained so that it continues to live together; 4) Eating together is a way to sit side by side in all circumstances, regardless of ethnic or religious differences. These teaching values are the basis for religious moderation in the Ndao Island community or Ndao people.